ANALISIS YURIDIS PENANGKAPAN DUTA BESAR INGGRIS OLEH OTORITAS IRAN BERDASARKAN VIENNA CONVENTION ON DIPLOMATIC RELATIONS 1961 - Agung Prayoga; Evi Deliana; Adi Tiara Putri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
This paper aims to discuss how the juridical analysis of the case of the arrest of the British Ambassador to Iran named Rob Macaire, the ambassador was arrested on January 11, 2020 near Amir Kabir University. The arrest was carried out by Iranian authorities on the allegation that Rob Macaire had instigated the anti-government era that broke out in Tehran at that time, it happened because the public was disappointed with the Iranian authorities who made the mistake of shooting the Boeing 752 plane belonging to Ukraine. The arrests carried out by the Iranian authorities had no clear reason and were not supported by solid evidence, the arrests were made on accusations that were not necessarily a form of violation of international treaties, namely article Vienna Convention on Diplomatic Relations 1961 (Vienna Convention 1961) regarding Diplomatic Relations, which regulates that an Ambassador or a diplomatic official cannot be contested, whether arrested or detained.This type of research is normative legal research, namely using literature case studies in data search. In this study the authors conducted research on the principles of law, namely the principle of immunity and the principle of Pacta suntservanda. This research is a descriptive research, which is a research method that describes the actual situation at the time of the research through data collection which is then interpreted to one another in order to obtain the formulation and analysis of an existing problem. Analysis of the data used by researchers and this is qualitative data analysis, namely analysis which does not use statistics or other things, but researchers simply describe descriptively of the data obtained.The results of this study can be concluded into three main points. First, based on the 1961 Vienna Convention on Diplomatic Relations, that the arrest of the British ambassador by the Iranian Authority on the accusation that the ambassador committed anti-government incitement was declared wrong, the arrest was not supported by evidence that strong but only accusations and an ambassador has immunity from being arrested and detained in the host country. Second, the arrest made by the Iranian Authority is a form of violation of the 1961 Vienna Convention, this raises the responsibility of the state, this can be in the form of an apology by Iran to the British ambassador and to Britain for the incident and ensuring that it will not be repeated and Iran can sanction its Authorities who make arrests on the basis of charges. Third, actions that a recipient country should be able to take if a representative in the receiving country commits an offense, namely by making a persona non grata declaration of the diplomatic official.Keywords: Arrest, Detention, Ambassador, Responsibility